(untitled) (CIPEEX, 2025)
This study aims to analyze the employer’s civil liability in cases of accidents at work, discussing the legal obligations regarding compensation for damages suffered by workers. The focus is to evaluate the employer’s role in preventing accidents and liability for negligence or non-compliance with safety standards, as well as the legal mechanisms for compensating physical, psychological and material damages. The research was based on an analysis of Brazilian jurisprudence and legislation, in particular the Consolidation of Labor Laws (CLT) and the Civil Code, in addition to international worker protection conventions. Court cases involving workplace accidents were also reviewed to identify decision patterns and understand how courts treat employer civil liability. Finally, the research analyzed official data and data from non-governmental organizations to understand the scenario and number of work accidents in Brazil. The results indicate that, according to Brazilian legislation, the employer has the obligation to provide a safe work environment, adopting all necessary measures to prevent accidents. When an accident occurs at work, the employer’s civil liability may arise if negligence, recklessness or omission in relation to the worker’s safety is proven. The research revealed that, in cases where the employer does not comply with safety standards, the worker has the right to compensation for damages, which may include compensation for material damages (such as medical expenses and loss of income) and moral damages (such as suffering emotional). It has been noted, however, that on many occasions workers face difficulties in proving the employer’s negligence and proceedings can be long and costly. The study concludes that the employer can be held responsible in cases of action or omission that lead to an accident at work, considering that it is up to him to guarantee a safe and risk-free working environment. It is also up to the employer to monitor and strictly apply safety standards. To minimize workplace accidents and reduce litigation, it is essential that employers invest in prevention through training to provide adequate safety equipment and an organizational culture that prioritizes the safety and well-being of its employees.